Governance's effects on innovation processes: The experience of EIP AGRI's Operational Groups (OGs) in Italy - Francesca Giarè; Anna Vagnozzi (Italian Review of Agricultural Economics (REA), 2021)
In this programming period, the most important initiative of the European agriculture innovation policy is the European Innovation Partnership for Agricultural Productivity and Sustainability (EIP AGRI) that is based on an interactive approach to innovation. The paper defines the theoretical framework of this approach and attempts to understand how the governance has facilitated or hindered this intervention. A comparative analysis of the Rural Development Programmes of four Italian Regions (Veneto, Emilia-Romagna, Umbria and Basilicata) was conducted, with particular attention to the rules and implementation criteria of the specific actions that financed the EIP AGRI projects (Sub-measures 16.1 and 16.2). The analysis shows the effects of regional governance on crucial factors of the EIP AGRI theoretical approach: co-creation of innovation between research and practice, centrality of farms and territories' needs, promotion of relations and networks, interactive action between the actors in the innovation chain. The Regions have paid different attention to the characteristics of this approach to the innovation; some factors are pursued by all Regions, while others have not yet been transposed and implemented. Some of these are clear and have been implemented through adequate rules and criteria, while for others, the appropriate implementation methods have not been identified and so the EIP AGRI projects are not consistent with the approach. The main notable conclusion is that all the Regions examined are substantially consistent with the dimensions of interactive approach that emerge from the international literature. Nevertheless, different methods and degrees of consistency have been highlighted.
Keywords: Q16; Q18; O13; 330; Agricultural Innovation Process; innovation governance; EIP-AGRI; multi-actor approach; interactive approach